2 Optimizing patient selection for endovascular treatment in acute ischemic stroke (SELECT): a prospective non-randomized multicenter cohort study of imaging selection. (July 2018) - Sarraj, A; Hassan, A; Gupta, R; Sitton, C; Grotta, J; Cai, C; Cutter, G; Imam, B; Reddy, S; Parsha, K; Vora, N; Abraham, M; et al.
Abstract : Background: Endovascular thrombectomy RCTs used different imaging selection modalities and criteria. Early window (0–6 hours) trials mostly used simple CT, while DAWN and DEFUSE3 utilized advanced perfusion images (CTP/MRP) beyond 6 hours. Thus, optimal imaging selection criteria for thrombectomy is unknown. Method: In this multicenter prospective cohort study, consecutive anterior-circulation large vessel occlusion patients up-to-24 hours from last-known-normal were enrolled in 9 centers (January/16–February/18). All patients received CT and CTP with mismatch determination using RAPID software. Treating physicians documented imaging selection modality prior to thrombectomy. Patients were divided based on selection modality into CT versus CTP groups. A blinded independent core-lab adjudicated imaging profiles defined a priori (Good CT=ASPECTS≥6, Good CTP=core vol<70 cc, mismatch-volume ≥10 cc and mismatch-ratio >1.2). The primary outcome (90 day mRS=0–2) was compared between the CT and CTP groups and for different CT and CTP profiles. Results: Of 445 patients enrolled, 341 received thrombectomy (figure 1). Median/IQR age=66/57–77, NIHSS=17/12–21, LSN-to-GP=3.8 hours/2.6–5.7 (range=1.2–17.6). 20% had ICA occlusions, 62% M1, and 18% M2. Selection modality was CT in 42% and CTP in 58%, with similar good outcome (CT=53.3% vs 54.3%=CTP, aOR=0.6, 95% CI: 0.3 to 1.5, p=0.3, figure 2a). There was no interaction with time, early vs late window, p=0.1. 87% had good CT and 89.6% had good CTP with comparable good outcome (CT=55.7% vs CTP=57.3, aOR=2.2, 95% CI: 0.5 to 10.9, p=0.3, figure 2b). In early window, the good outcome rates were 54.9% for good CT and 58% for good CTP; for late window, they were 58.7% and 57.1%, respectively. There was no interaction with time (p=0.5). 16.8% would have been excluded from thrombectomy based on either CT or CTP only; 40.5% of them had good outcome. Of patients potentially excluded by CT but qualified by CTP, 50% had good outcomes with thrombectomy and 33% with medical management only. Similarly, of those excluded by CTP but treated by CT, 27.8% had good outcomes with and 0% without thrombectomy, respectively (table 1). Furthermore, discordant profiles patients (Good CT-Poor CTP and Poor CT-Good CTP) with good reperfusion (mTICI ≥2b) had higher good outcome rates, compared to mTICI <2b: 33.3% vs 0% and 52.6% vs 40%, respectively. Thrombectomy did not confer good outcomes in patients with Poor CT-Poor CTP. Conclusion: Good outcome rates were comparable in patients selected for thrombectomy by CT versus CTP and those with good imaging profiles on either CT or CTP irrespective of the treatment time window, early or late. However, both imaging modalities excluded a similar number of patients who may benefit from the intervention. Our results will be validated in a randomized trial (SELECT2). Disclosures: A. Sarraj: 1; C; Principal Investigator of the SELECT and SELECT 2 trials – unrestricted grant from Stryker Neurovascular to UT McGovern-Houston. 2; C; Consultant and Speaker for Stryker Neurovascular, Advisory Board – Stryker Neurovascular. 6; C; UT-Memorial Hermann Center PI for the Trevo Registry and DEFUSE 3 TRIAL, Steering Committee –ASSIST Registry. A. Hassan: None. R. Gupta: None. C. Sitton: None. J. Grotta: None. C. Cai: None. G. Cutter: None. B. Imam: None. S. Reddy: None. K. Parsha: None. N. Vora: None. M. Abraham: None. R. Edgell: None. F. Hellinger: None. D. Haussen: None. H. Kamal: None. L. McCullough: None. M. Lansberg: None. S. Savitz: None. G. Albers: None.